2014
DOI: 10.1002/anie.201400560
|View full text |Cite
|
Sign up to set email alerts
|

Combining Rhodium and Photoredox Catalysis for CH Functionalizations of Arenes: Oxidative Heck Reactions with Visible Light

Abstract: Direct, oxidative metal-catalyzed C-H functionalizations of arenes are important in synthetic organic chemistry. Often, (over-)stoichoimetric amounts of organic or inorganic oxidants have to be used in these reactions. The combination of rhodium and photoredox catalysis with visible light allows the direct C-H olefination of arenes. Small amounts (1 mol%) of a photoredox catalyst resulted in the efficient C-H functionalization of a broad range of substrates under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(71 citation statements)
references
References 85 publications
1
62
0
8
Order By: Relevance
“…Subsequently, Rueping demonstrated that photoredox catalysis could also aid Ru- and Rh-catalyzed oxidative Heck reactions in a mechanistically analogous manner. 91,92 …”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 99%
“…Subsequently, Rueping demonstrated that photoredox catalysis could also aid Ru- and Rh-catalyzed oxidative Heck reactions in a mechanistically analogous manner. 91,92 …”
Section: Metallaphotoredox Catalysis: C–c Bond Formationmentioning
confidence: 99%
“…The details of the oxidation have not yet been elucidated, but given the two-electron oxidation state change required, the mechanism must presumably be somewhat more complicated than a simple bimolecular photoinduced single electron transfer. Rueping has utilized a similar design strategy in oxidative Heck reactions of aryl amides 252 and phenols 253 catalyzed by rhodium and ruthenium, respectively.…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%
“…In 2014, the Rueping research group combined the rhodium catalyzed ortho C-H activation with ruthenium driven photoredox catalysis (Figure 17). 53 Benzamide derivatives (51) were alkenylated directly using the alkenes. In the proposed mechanism, the role of stoichiometric amount of oxidating agent deputized by Ru photocatalytic cycle.…”
Section: C-h Activation and Photoredox Dual Catalysismentioning
confidence: 99%